Prevalensi Infeksi Human Papilloma Virus Tipe 16 dan 18 serta Lesi Prakanker dari Pemeriksaan Pap smear Berbasis Cairan pada Pasien dengan Infeksi Human Immunodeficiency Virus - Iin Indrayani Maker Luh Putu; Moestikaningsih .; Ketut Suwiyoga; Mona Mariana (Perhimpunan Dokter Spesialis Patologi Indonesia (IAPI), 2016)
Background Bali province is the sixth highest Human Immunodeficiency Virus (HIV) prevalence in September 2012, which was 5871 cases, among them were 1227 women. HIV infected women with latent Human Papilloma Virus (HPV) in cervical uterine will have 10-20 times risk to develop cervical precancerous and cancer. The high risk group of HPV including HPV type 16 and 18. The aim of this study is to get the epidemiologic data of HPV type 16 and 18 prevalency and precancerous cervical lesion prevalency from liquid based pap smear of HIV infected women. Methods This was a descriptive prospective cross sectional study. Fifty samples were collected by concecutive sampling from liquid based pap smear of HIV infected women. Two smears were made from each sample, stain with Papanicolaou, then examination of HPV (especially type 16 and 18) was conducted by Polymerase Chain Reaction (PCR) from the remaining sample of each patient. The results of pap smear and PCR examination were grouped into whether there is positive or negative of HPV infection, type of HPV, positive or negative precancerous lesion and age groups. Results From 50 samples, 60% were HPV positive (13.3% type 16, 10% type 18, and 6.7% type 16 and 18). From 30 HPV positive samples, there were 11 (11.3%) precancerous lesions, and from 20 HPV negative samples, there were 1 (5.0%) precancerous lesions. The youngest HPV infected women with precancerous lesion was 19 years old. Conclusion Prevalency of HPV was found in more than half HIV infected samples, which type 16 was found higher than type 18. Precancerous lesions were higher in HIV with HPV infected women. Key words : Cervical precancerous lesion, Human immunodeficiency virus, human papilloma virus, liquid based pap smear, PCR, type 16 and 18